Banking selection criteria : a study among muslims in Kelantan - Siti Fariha Muhamad; Nurul Atika Anuar; Mohd Khairy Kamarudin; Nurul Ashykin Abd Aziz; Afifah Hanim Md Pazil; Mohd Zulkifli Muhammad (2015)
The main purpose of this study is to examine the differences of selection criteria that are considered